PENGARUH MERK DAN RASIO CAMPURAN ANTI GORES TERHADAP KUALITAS HASIL PELAPISAN MATERIAL LOGAM - ikhwanul Qiram; Fawaizul Umam; Adi Pratama (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
Paint is a liquid used to coat the surface of an object with the aim of decorative, reinforcing or protective of the material. Anti-scratch or varnish is a paint made from a hydrocarbon polymer without a color pigment. This study aims to determine the effect of the brand and the ratio of the anti-scratch mixture on the quality of the metal coating. The workpiece used is a 0.5 mm galvanized plate with a size of 10 cm x 10 cm. In this study, three variations of the ratio of anti-scratch and thinner mixtures will be carried out, namely 1: 1, 1: 1.25 and 1: 1.5 using the brands MTT, BLKT, WS. Spraying variations include spraying 1 sec (2x spraying), 2 secs (4x spraying), 3 sec (6x spraying). From the data collection process, two measurements will be taken, the first, the gloss test using a lux meter and a color density test. The gloss test was carried out by irradiating using three tilt angles, namely 50 °, 55 ° and 60 °. To test the color density using the Coolphptools Software. The highest gloss results occurred on the WS brand with a mixture ratio of 1: 1 resulting in a value of 9770 (lux) at an angle of 60 ° with a spray time of 2 seconds (4 times spray). The lowest yield occurred for the MTT brand producing a value of 4170 at an angle of 50 ° with a spray time of 3 seconds (6 times the spray). The results of this study generally show that the brand and the ratio of the anti-scratch mixture have an effect on the coating of metal materials